1989
DOI: 10.1083/jcb.108.6.2369
|View full text |Cite
|
Sign up to set email alerts
|

A new 82-kD barbed end-capping protein (radixin) localized in the cell-to-cell adherens junction: purification and characterization.

Abstract: An 82-kD protein has been purified from the undercoat of the adherens junction isolated from the rat liver. The purification scheme includes low salt extraction followed by DEAE-cellulose ion exchange, DNase I- actin affinity, and carboxyl methyl-cellulose ion exchange chromatographies. The purified 82-kD protein was essentially free of contaminants as judged by SDS-PAGE combined with silver staining. The substoichiometric 82-kD protein largely inhibited the actin filament assembly; when the molar ratio of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
138
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(149 citation statements)
references
References 43 publications
(68 reference statements)
8
138
0
2
Order By: Relevance
“…Talin links the fibronectin receptor to the actin cytoskeleton via vinculin and a-actinin (Rees et al, 1990). Radixin, one ERM family member originally isolated from the adherens junction of hepatocyte, has shown actin-binding activity via capping the barbed end of actin filament in vitro (Tsukita et al, 1989). Those authors subsequently showed that radixin is highly concentrated at the cleavage furrow in a variety of culture cells during cytokinesis, which implies that radixin might modulate the actin filament-plasma membrane interaction at the furrow (Sato et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Talin links the fibronectin receptor to the actin cytoskeleton via vinculin and a-actinin (Rees et al, 1990). Radixin, one ERM family member originally isolated from the adherens junction of hepatocyte, has shown actin-binding activity via capping the barbed end of actin filament in vitro (Tsukita et al, 1989). Those authors subsequently showed that radixin is highly concentrated at the cleavage furrow in a variety of culture cells during cytokinesis, which implies that radixin might modulate the actin filament-plasma membrane interaction at the furrow (Sato et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Radixin is a member of the ERM (ezrin/radixin/ moesin) family of proteins (Mangeat et al, 1999;Sato et al, 1992), which was first isolated as a constituent of adherence junctions in rat liver (Tsukita and Hieda, 1989). Ezrin was first purified as a component of intestinal microvilli that is tyrosine-phosphorylated by epidermal growth factor receptor (EGFR; Bretscher, 1989), and moesin was originally identified as a heparin-binding protein (Lankes and Furthmayr, 1991).…”
mentioning
confidence: 99%
“…Identification of genes that are involved in tumorigenesis and in the progression of lung cancer will be required to formulate more effective therapies. One approach to the identification of such genes is to use differential display analysis (Bauer et al, 1993;Liang et al, , 1993Sager et al, 1993;Yoshikawa et al, 1998).Radixin is a member of the ERM (ezrin/radixin/ moesin) family of proteins (Mangeat et al, 1999;Sato et al, 1992), which was first isolated as a constituent of adherence junctions in rat liver (Tsukita and Hieda, 1989). Ezrin was first purified as a component of intestinal microvilli that is tyrosine-phosphorylated by epidermal growth factor receptor (EGFR; Bretscher, 1989), and moesin was originally identified as a heparin-binding protein (Lankes and Furthmayr, 1991).…”
mentioning
confidence: 99%
“…The localization of radixin is slightly distinct from ezrin and moesin since it was originally identified as a component of adherent junctions. It is also localized at focal contacts, in the cleavage furrow and the contractile ring of cultured cells [13,14] . However, these localizations are controversial [18] .…”
Section: Localization Of the Erm Proteinsmentioning
confidence: 99%
“…Ezrin is highly concentrated in intestine, stomach, lung and kidney although moesin is prominent in lung and spleen, and radixin in liver and intestine [13,14] . Ezrin is expressed in epithelial and mesothelial cells while moesin is expressed in endothelial cells [12] .…”
Section: Localization Of the Erm Proteinsmentioning
confidence: 99%